A CASE STUDY OF INDONESIAN WOMEN'S POSITIONS IN FAMILY INSTITUTION ASDEPICTED IN PRINT ADVERTISEMENTS: A Critical Discourse Analysis of print Advertisements Displayed in an Indonesian Women's Magazine - Penni Patmawati R., - (2008)
The present study, entitled A Case Study of Indonesian Women's Positions in Family Institution as Depicted in Print Advertisements (A Critical Discourse Analysis of print Advertisements Displayed in an Indonesian Women's Magazine), describes how the advertisement texts displayed in a women's magazine represent the Indonesian women's positions in family. The data were obtained from three editions of an Indonesian weekly women's magazine, published during the period of September to December 2006. The study employed qualitative principles using Fairclough's framework of CDA. Hallidayan's Systemic Functional Grammar and Kress and Van Leeuwen's theories of reading images are used as the tools of analysis for analyzing the texts under study. The results show that the representations of Indonesian women's positions in family institution depicted in the texts are varied according to the products or services being advertised in the advertisements. They are represented as mothers who do the domestic tasks, are in charge in taking care of and watching the children, have career, and have the liberty to manage their own money. However, the advertisement texts mostly represent the Indonesian women as mothers in the family who are in charge for social activity types related to domestic works, especially taking care of children.